Stalling Beneath the Summit: Why is Progress Towards Inclusion Proving Elusive? - Rose, Richard (REACH: Journal of Inclusive Education in Ireland, 2021)
Despite considerable efforts to increase inclusion in schools, a small but significant number of pupils with special educational needs continue to require segregated provision. Why does the attainment of full inclusion remain elusive?